A Critique on the Book A Glance at the Literary Developments after the Victory of the Islamic Revolution in Iran - Fatemeh Rakei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book A Glance at the Literary Developments after the Victory of Islamic Revolution in the Realm of Poetry and Fiction by Bahjat-o- Sadat Hejazi was published in 2015 by the Elmi- Farhangi publications. The present article has been written to introduce and criticize the aforementioned book. The outcome of the study shows that the book as a whole from both aspects is poor and fails to meet the requested standards. For this reason, it deserves not to be placed among other references before being reviewed drastically. Obviously, it would be useful provided that all the deficiencies be removed.